The analytical design of a folded waveguide traveling wave tube and small signal gain analysis using madey's theorem - Mohd Fareq, Abd Malek, Dr. (Progress In Electromagnetics Research (PIER), 2012)
Link to publisher's homepage at http://www.jpier.org/PIER/